High-Temperature, Dry Scrubbing of Syngas with Use of Mineral Sorbents and Ceramic Rigid Filters - Mateusz Szul; Tomasz Iluk; Aleksander Sobolewski (Energies, 2020)
In this research, the idea of multicomponent, one-vessel cleaning of syngas through simultaneous dedusting and adsorption is described. Data presented were obtained with the use of a pilot-scale 60 kWth fixed-bed GazEla reactor, coupled with a dry gas cleaning unit where mineral sorbents are injected into raw syngas at 500−650 °C, before dedusting at ceramic filters. The research primarily presents results of the application of four calcined sorbents, i.e., chalk (CaO), dolomite (MgO−CaO), halloysite (AlO−MgO−FeO), and kaolinite (AlO−MgO) for high-temperature (HT) adsorption of impurities contained in syngas from gasification of biomass. An emphasis on data regarding the stability of the filtration process is provided since the addition of coating and co-filtering materials is often necessary for keeping the filtration of syngas stable, in industrial applications.